Real-World Evidence From More Than 1000 Patients Treated With Adalimumab For Moderate-to-Severe Psoriasis in the Czech Republic - Kojanova, Martina; Cetkovska, Petra; Strosova, Daniela; Fialova, Jorga; Arenberger, Petr; Dolezal, Tomas; Gkalpakiotis, Spyridon; BIOREP Study Group (Dermatology and therapy, 2021)
INTRODUCTION: The study aimed to evaluate the real-world effectiveness of adalimumab as well as investigate the persistence of treatment and identify factors, which may affect it. METHODS: More than 1150 patients (4363.1 patient-years) with psoriasis who had been treated with adalimumab since the start of the BIOREP registry in the Czech Republic were included in this analysis. Treatment effectiveness was defined as improvement in Psoriasis Area and Severity Index (PASI). The analysis was performed during the years 2005 and 2018. Patients were on on-label dose. RESULTS: After 12 and 96 months of therapy, 84% and 88% of patients had a 75% reduction in PASI score from baseline, respectively. Drug survival was analyzed according to the number of previous biological therapies, and results showed 75% and 58.1% survival rate for biologically naïve patients in the 20th and 80th month of treatment, respectively. The negative predictors of adalimumab survival were the female gender, obesity, baseline PASI score and the number of previous biological therapies. CONCLUSIONS: Baseline factors including PASI, number of previous biological therapies, and sex were associated with shorter adalimumab survival. This long-term study shows that adalimumab is effective and has high treatment persistence.
Keywords: Adalimumab; Registries; Persistence of treatment; BIOREP; Long-term effectiveness; Psoriasis